Rituximab as Single Agent in Primary MALT Lymphoma of the Ocular Adnexa. (6th September 2015) - Annibali, Ombretta; Chiodi, Francesca; Sarlo, Chiara; Cortes, Magdalena; Quaranta-Leoni, Francesco M.; Quattrocchi, Carlo; Bianchi, Antonella; Bonini, Stefano; Avvisati, Giuseppe
Abstract : Ocular Adnexal Lymphomas are the first cause of primary ocular malignancies, and among them the most common are MALT Ocular Adnexal Lymphomas. Recently systemic immunotherapy with anti-CD20 monoclonal antibody has been investigated as first-line treatment; however, the optimal management for MALT Ocular Adnexal Lymphomas is still unknown. The present study evaluated retrospectively the outcome of seven consecutive patients with primary MALT Ocular Adnexal Lymphomas, of whom six were treated with single agent Rituximab. All patients received 6 cycles of Rituximab 375 mg/mq every 3 weeks intravenously. The overall response rate was 100%; four patients (67%) achieved a Complete Remission, and two (33%) achieved a partial response. In four patients an additional Rituximab maintenance every 2-3 months was given for two years. After a median follow-up of 29 months (range 8–34), no recurrences were observed, without of therapy- or disease-related severe adverse events. None of the patients needed additional radiotherapy or other treatments. Rituximab as a single agent is highly effective and tolerable in first-line treatment of primary MALT Ocular adnexal Lymphomas. Furthermore, durable responses are achievable with the same-agent maintenance. Rituximab can be considered the agent of choice in the management of an indolent disease in whom the "quality of life" matter is of primary importance.